Harmonizing Interests in Tourism Development: A Study of Actor Collaboration through Islamic Principles - Iswadi, Jumari (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to explore the forms of collaboration between actors in tourism development through an analysis that integrates the principles of Islamic educational management, namely syura (consultation), ukhuwah (brotherhood), and tawazun (balance). Using a literature review approach, this research analyzes the roles of tourism development actors such as the Department of Tourism, Pokdarwis (Tourism Awareness Groups), the community, the DPR (House of Representatives), and businesspeople/investors. The key findings reveal that collaboration between actors faces various challenges, including conflicting interests and a lack of effective communication. The study also highlights how the principles of Islamic educational management can enhance the effectiveness of collaboration through more inclusive participation, more harmonious relationships, and a balance between economic development and the preservation of culture and the environment. The integration of these concepts is expected to create stronger and more sustainable synergy among tourism development actors. This research offers a new perspective that emphasizes the importance of moral and ethical approaches in development collaboration.